2016
DOI: 10.1016/j.bjm.2016.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Volatile metabolites produced from agro-industrial wastes by Na-alginate entrapped Kluyveromyces marxianus

Abstract: The aim of this study was to evaluate the effects of alginate entrapment on fermentation metabolites of Kluyveromyces marxianus grown in agrowastes that served as the liquid culture media. K. marxianus cells entrapped in Na-alginate were prepared using the traditional liquid-droplet-forming method. Whey and pomaces from processed tomatoes, peppers, and grapes were used as the culture media. The changes in the concentrations of sugar, alcohol, organic acids, and flavor compounds were analyzed using gas chromato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 30 publications
1
8
0
2
Order By: Relevance
“…Biofilm-detached cells produced lower levels of 2-PEA (15.39 mg/L). In this study, it was found that K. marxianus yeast biofilm-detached cells produced 2-phenethyl butanoate, and phenethyl isobutyrate which are usually found in low amounts and are sought after by the food industries for their sensory impact on foods [ 33 ]. Ketones and phenols were produced only by biofilm-detached cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Biofilm-detached cells produced lower levels of 2-PEA (15.39 mg/L). In this study, it was found that K. marxianus yeast biofilm-detached cells produced 2-phenethyl butanoate, and phenethyl isobutyrate which are usually found in low amounts and are sought after by the food industries for their sensory impact on foods [ 33 ]. Ketones and phenols were produced only by biofilm-detached cells.…”
Section: Resultsmentioning
confidence: 99%
“…Phenethyl propionate (rose, floral, honey) is commonly not synthesized by S. cerevisiae . The production of this compound has been described in some non- Saccharomyces such as L. thermotolerans , Torulaspora delbrueckii , and K. marxianus [ 33 , 42 ]. In particular, Güneser et al [ 33 ] evaluated the effects of alginate entrapment on fermentation metabolites of K. marxianus grown in agrowastes that served as the liquid culture media.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest pH decrease was observed in runs 3, 4, 7-11, in which the initial pH was higher (5.5-6.5), which can also mean that those conditions enabled not only ethanol production but also secondary metabolites, which is undesirable when ethanol is the main product of interest (Güneser, Karagül-Yüceer, Wilkowska, & Kregiel, 2016). Organic acids were identified in the runs, with concentrations in the range of: 0.5 to 5 g L -1 (AA), 1 to 3 g L -1 (propionic), 0.5 to 2.5 g L -1 (valeric), 0.5 to 6 g L -1 (lactic), 0.5 to 3 g L -1 (formic), and 0.5 to 2.3 g L -1 (butyric).…”
Section: Ethanol Production Kinetics Of Alcoholic Fermentationsmentioning
confidence: 94%
“…A pesar de que en esta sección, uno de los objetivos principales es la producción de etanol, la identificación y cuantificación de los compuestos volátiles generados es fundamental para las características organolépticas de la bebida (Dragone et al, 2009). En estas bebidas se identificaron compuestos de sabor tales como alcohol isoamílico (plátano), acetato de isoamilo (afrutado, plátano), alcohol feniletílico (rosa), acetato de feniletilo (floral), entre otros (Dragone et al, 2009;Gantumur et al, 2022;Guneser et al, 2016;Risner, Tomasino, Hughes, & Meunier-Goddik, 2019). La productividad de los compuestos volátiles depende del tipo de residuos agrícolas (Guneser et al, 2016).…”
Section: Producción De Bebidasunclassified